Genetic Drift and Host-Adaptive Features Likely Underlie the Cladogenesis of Insect-Associated Lachnospiraceae. (9th June 2022) - Vera-Ponce de Leon, Arturo; Schneider, Mathias G; Jahnes, Benjamin C; Sadowski, Victoria; Camuy-Vélez, Lennel A; Duan, Jun; Sabree, Zakee L
Abstract: Phylogenetic and functional group analyses of the genomes of anaerobic bacteria isolated from Periplaneta americana digestive tracts suggest that they represent novel Lachnospiraceae genera. PAL113 and PAL227 isolate genomes encoded short-chain fatty acid biosynthetic pathways and plant fiber and chitin catabolism and other carbohydrate utilization genes common in related Lachnospiraceae species, yet the presence of operons containing flagellar assembly pathways was among several distinguishing features. In general, PAL113 and PAL227 isolates encode an array of gene products that will enable them to thrive in the insect gut environment and potentially play a role in host diet processing. We hypothesize that the cladogenesis of these isolates can be a result of their oxygen sensitivity and reliance upon the host for dispersal and genetic drift and not necessarily a result of an ongoing mutualism.